Impact of Human Resource Management and Digital Marketing Strategies on Profitability: a Statistical Evaluation in Well-Performing Companies - Steviani Batti (Digital Innovation : International Journal of Management, 2024)
This study explores the impact of product and service innovation, operational efficiency, customer satisfaction, human resource management, and digital marketing strategies on the profitability of companies. Utilizing a quantitative research methodology, data was collected through surveys and company financial reports and analyzed using statistical techniques, including linear regression analysis. The findings reveal that product and service innovation significantly enhances profitability, emphasizing the importance of continuous innovation. Operational efficiency, measured through lower operational costs, directly correlates with increased profit margins. Furthermore, a strong positive relationship exists between customer satisfaction and profitability, highlighting the importance of customer-centric strategies. Human resource management practices that promote employee satisfaction and productivity are also found to significantly impact profitability. Lastly, the adoption of digital marketing strategies is shown to boost sales volume and market reach, contributing positively to financial performance. These results suggest that companies should adopt a holistic approach to strategy development, integrating innovation, operational efficiency, customer satisfaction, human resource management, and digital marketing to enhance profitability. The study underscores the need for companies to continuously evolve and adapt to market changes to sustain competitive advantage and long-term success.